2015
DOI: 10.3171/2014.10.jns14139
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife radiosurgery for posterior fossa meningiomas: a multicenter study

Abstract: abbreviatioNs CI = confidence interval; CN = cranial nerve; CPA = cerebellopontine angle; GKRS = Gamma Knife radiosurgery; HR = hazard ratio; OR = odds ratio; SRS = stereotactic radiosurgery. obJect Posterior fossa meningiomas represent a common yet challenging clinical entity. They are often associated with neurovascular structures and adjacent to the brainstem. Resection can be undertaken for posterior fossa meningiomas, but residual or recurrent tumor is frequent. Stereotactic radiosurgery (SRS) has been us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 60 publications
7
51
1
Order By: Relevance
“…Importantly, the authors in that study reported tumor control rates of 95%, 92%, and 81% at 3, 5, and 10 years after radiosurgery, respectively. 20,22 Similarly, we found that GKRS as the initial treatment for small, mildly symptomatic lesions as well as recurrent or progressive tumors resulted in excellent disease control, and no patient treated initially with GKRS experienced progression over the follow-up period. Low rates of progression/recurrence suggest that longterm disease control for these low-grade lesions is possible with the outlined treatment algorithm, even in the setting of STR, and supports the goal of preserving neurological function whenever possible to maximize patient quality of life.…”
Section: 25mentioning
confidence: 69%
See 3 more Smart Citations
“…Importantly, the authors in that study reported tumor control rates of 95%, 92%, and 81% at 3, 5, and 10 years after radiosurgery, respectively. 20,22 Similarly, we found that GKRS as the initial treatment for small, mildly symptomatic lesions as well as recurrent or progressive tumors resulted in excellent disease control, and no patient treated initially with GKRS experienced progression over the follow-up period. Low rates of progression/recurrence suggest that longterm disease control for these low-grade lesions is possible with the outlined treatment algorithm, even in the setting of STR, and supports the goal of preserving neurological function whenever possible to maximize patient quality of life.…”
Section: 25mentioning
confidence: 69%
“…6,20 While aggressive and complete resection of meningiomas is curative, tumors arising within the CPA present unique surgical challenges com- pared with supratentorial lesions, given their close association with critical neurological and vascular structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In case of incomplete resection, recurrent, or a priori nonresectable tumors, radiotherapy is the treatment of choice. To date, two radiotherapy regimes are established: stereotactic radiosurgery (SRS) and full-course fractionated stereotactic radiotherapy (FSRT) [1][2][3]. While SRS (mostly performed with doses of 12-15 Gy) is limited to small lesions distant to critical structures, FSRT can be applied even in larger lesions in close proximity to organs at risk, using total doses of 50.4-57.6 Gy in fractions of 1.8 Gy.…”
mentioning
confidence: 99%